The single server vacation queue with geometric abandonments and Bernoulli’s feedbacks - Vijayalakshmi, V; Kalidass, K (International Journal of Engineering and Technology, 2018)
In this article the behaviour of a single server vacation queue with geometric abandonments and Bernoulliâ€™s feedbacks is carried out and various important performance measures are derived. Some numerical experiments are presented to study how the parameters of the model influence the state of the system.Â